Halalan thayyiban and circular economy: A halal centric paradigm for sustainable resource management in Brunei - Nabilah Ulfah Mujib; Hamzah Mohd. Salleh (Journal of Halal Industry Studies, 2026)
The halal industry is increasingly expected to ensure not only halal-certified products and services but also sustainable, ethical, and environmentally responsible operations. Although the circular economy (CE) promotes resource efficiency through reuse, recycling, and waste reduction, existing CE models largely emphasize technical and economic dimensions while overlooking religious and ethical values relevant to the halal sector. In Brunei Darussalam, food waste accounts for approximately 32% of total landfill waste, while only 11.3% is recycled, raising concerns about the Sungai Paku Engineered Landfill's projected capacity by 2030. This study addresses the absence of a halal-oriented food waste management model by examining the synergies between the principles of Halalan Thayyiban and the circular economy. Using a qualitative approach, thematic analysis was conducted on relevant literature and Islamic sources. The findings demonstrate that Islamic ethical principles, particularly safety, cleanliness, responsibility, and waste prevention, grounded in the objectives of Maqasid al-Shari'ah, reinforce circular economy practices and provide a stronger ethical foundation for sustainable food waste management. This study contributes by proposing a halal-centric conceptual perspective that integrates Islamic ethical values with circular economy strategies within Brunei's halal industry. The proposed framework offers practical guidance for policy development and implementation while supporting sustainable development, particularly responsible consumption and production (SDG 12) and climate action (SDG 13).